PENINGKATAN GENERASI QURâ€™ANI MELALUI PENGADAAN SANGGAR TAHFIDZ DI DESA KADUARA TIMUR KECAMATAN PRAGAAN KABUPATEN SUMENEP - Nurul Hidayati; Luthfatul Qibtiyah (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
The people in Kaduara Timur Pragaan Sumenep Village is a community that has good religious assets, this is evidenced by the existence of several activities carried out by the community such as holding tahlilan, maulidan, shalawatan and so on. This shows that religion in the village is quite good. In addition, the youth of the Al-Falah Mosque also play an active role in inviting other youth to always apply the values of Islamic teachings in individual or social life as an effort to spread Islam. High enthusiasm shown by elementary school children to come to the musholla or mosque to recite the Koran, but there is a lack of deepening of the Qur'an and tahfidz so that during the time waiting for the evening prayer the children only play so this service takes the initiative to carried out reforms and created a program â€œIncreasing the Qur'anic Generation through the Procurement of Tahfidz Studiosâ€. The program received a positive response and full support from the community and the village head to be held in mosques and prayer rooms. This service is carried out as a form of the Tri Dharma of higher education, namely doing community service, being part of meeting the needs of the community, in this case the service is carried out in the religious aspect.